Yinhua Pinggan Granules alleviate lung and intestinal damage in influenza virus-infected mice by modulating gut microbiota and its metabolites to activate the GPR43-MAVS-IRF3-IFN-β pathway - Zeng, Di; Zhou, Huifen; Wan, Haitong; Chen, Jing (Frontiers in Microbiology, 2025)
ObjectiveDerived from Ma Huang Decoction in the Shang Han Lun, Yinhua Pinggan Granules (YHPG) are used in traditional Chinese medicine for treating influenza. This study highlights the gut microbiota’s role in intestinal damage and acute lung injury from influenza virus infection, offering insights into influenza A virus prevention and treatment through the gut-lung axis.MethodsUsing a mouse model disrupted by a four-antibiotic regimen, we assessed survival, weight, lung, and spleen indices post-IAV infection. We evaluated lung and intestinal pathology, viral load, and protein expressions via H&E staining, RT-qPCR, and immunofluorescence. 16S rRNA sequencing and targeted metabolomics were utilized to uncover the impact of YHPG treatment on disrupted gut microbiota and its metabolites after H1N1 infection.ResultsH&E staining showed severe lung and intestinal damage in IAV-infected mice with disrupted gut microbiota. Immunofluorescence results demonstrated that relative depletion of gut microbiota might exacerbate colonic barrier damage in IAV-infected mice. YHPG restored microbiota diversity, increasing SCFA-producing bacteria, aligning with metabolite changes. Western blot and RT-qPCR showed activation of the GPR43-MAVS-IRF3-IFN-I pathway, linked to SCFA regulation.ConclusionYHPG alleviate influenza symptoms, promoting SCFA-producing bacteria and maintaining gut homeostasis. They modulate the GPR43-MAVS-IRF3-IFN-β pathway, suggesting novel treatment avenues for influenza through gut microbiota modulation.